Effect Of Final Irrigation Materials And Irrigation Techniques On Dental Root Fracture Resistance - Aspriyanti, Silva Eliana; Nari Ratih, Diatri; Widyastuti, Andina (Jurnal Kesehatan Gigi, 2025)
Teeth undergoing root canal treatment are at higher fracture risk due to changes in dentin’s mechanical properties from irrigation solutions, leading to erosion and reduced fracture resistance. This study evaluates the effects of various final irrigation solutions and techniques on fracture resistance in treated teeth. An experimental study used 24 mandibular premolars, divided into six groups, each treated with one of two irrigation solutions (17% EDTA or 0.2% chitosan nanoparticles) and one of three irrigation techniques (manual, sonic, ultrasonic). Fracture resistance was measured with a Universal Testing Machine, and results analyzed using two-way ANOVA and Post-Hoc LSD tests. Findings indicated both irrigation solution type and technique significantly affected fracture resistance (p0.05). The group treated with Chitosan Nanoparticles using manual agitation showed the highest fracture resistance, while the EDTA Ultrasonic group showed the lowest. These results highlight the importance of selecting irrigation solutions and techniques to enhance fracture resistance in root canal-treated teeth, with chitosan nanoparticles and manual techniques showing the best outcomes.